Poverty in China's rural areas: Temporary or chronic? - Thomas Glauben; Thomas Herzfeld; Scott Rozelle; Xiaobing Wang (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
Curbing poverty can surely be deemed to be one of the most eminent objectives on socio-political agendas. Progress in reducing worldwide poverty achieved in to date, however, makes rather sobering reading. China has considerably reduced the number of poor since commencement of economic reforms in the late 1970s. Still, there are ca. 170 million people affected by poverty. This paper investigates the issue whether poverty in China's rural areas is rather of a chronic or temporary nature and what the opportunities are of escaping poverty. Simultaneously, there are discussions whether certain factors rather favour or counteract chronic poverty. – – Die Bekämpfung von Armut kann sicherlich als eines der wichtigsten Ziele gesellschaftspolitischer Agenden angesehen werden. Die Bilanz der bisher erreichten Fortschritte bei der Bekämpfung der weltweiten Armut fällt allerdings ernüchternd aus. China reduzierte seit Beginn der ökonomischen Reformen Ende der 1970er Jahre in erheblichem Maße die Zahl der Armen. Dennoch sind immer noch ca. 170 Millionen Menschen von Armut betroffen. Dieser Beitrag befasst sich mit den Fragen, ob Armut in Chinas ländlichen Regionen eher chronischer oder temporärer Natur ist und welche Chancen bestehen, Armut zu entrinnen. Gleichzeitig wird diskutiert, ob bestimmte Faktoren chronische Armut eher begünstigen oder dieser entgegenwirken.
urn:nbn:de:gbv:3:2-32055
Keywords: 330; Ländliche Armut; China